KETAHANAN BEBERAPA KULTIVAR JAGUNG LOKAL TIMOR TERHADAP HAMA GUDANG Sitophilus zeamais. L - Nina Jeni Lapinangga; Jaqcualine A. Bunga; Jemrift H. H. Sonbai; Yosefus F. da Lopez (Politeknik Pertanian Negeri Kupang, 2019)
Corn kernels that are stored for a longer period are susceptible to pest infestation by Sithopilus zeamais. To overcome these problems, we need environmentally friendly pest control techniques, namely the use of resistant cultivars. This study aims to determine the level of resilience of 22 local Timor corn cultivars against the Sitophilus zeamais L. Pest. The results showed that the highest total population was found in the Muke Bunga Putih cultivar (121 individuals), Desa Kie Dusun 3 (107, 5 individuals), Silawan Kuning (109.5 individuals), Desa Oenlasi Dusun 4 (141.5 individuals), while the lowest total population were in the Haikesak Putih cultivar (11.5 individuals), Tastim 1 Putih (15 individuals), and Tasifeto Timor Biboki Anleu Putih (17 individuals). Bunga Merah Muke cultivar, Pulut Putih Muke cultivar, and Bunga Putih Fatumonas cultivar have the smallest development period (30 days), while Kie Dusun 1 and Malaka 2 Kuning cultivars have the largest development periods (35 days). There are 7 cultivars, namely Haikesak Putih, Tastim 1 Putih, Bunga Merah Fatumonas, Desa Kie Dusun 1, Malaka 1 Putih, Putih Fatumonas and Tasifeto Timur Biboki Anleu Putih that are resistant to S. zeamais pests. Keywords: cultivar, Timor local maize, Sitophilus zeamais. L